Chlorophyll content in plants and fruit yield of strawberry plants grown on mulching (Revista de Ciências Agroveterinárias, 2017)
This study aimed to evaluate productive characteristics and levels of photosynthetic pigments in two strawberry cultivars on different types of mulching, in an open cultivation system. The experiment was a 2 x 4 factorial completely randomized block design, with 2 varieties (Camarosa and Camino Real) and 4 ground covers (black low-density polyethylene, silver low-density polyethylene, non-woven and no mulching), with three replications. The cultivars were analyzed for chlorophyll a and b content, total chlorophyll, and chlorophyll a/b ratio, number of fruits per plant, yield (ton ha-1), weight fruit mass, soluble solids (ºBrix), total acidity, pH and soluble solids/total acidity ratio. The Camarosa showed higher yield than cv. Camino Real. The silver low-density polyethylene and non-woven mulching treatment exhibited negative results, and are not recommended for the cultivation of Camarosa and Camino Real strawberries. The black low-density polyethylene mulching was the most recommended for growing such cultivars. Among the types of mulchings evaluated, the black low-density polyethylene achieved the best results and it is recommended for the Camarosa and Camino Real strawberry cultivars.
Keywords: Fragaria; ground cover; varieties.